Pursuing Happiness : American Consumers in the Twentieth Century - Lebergott, Stanley (Book collections on Project MUSE., 2014)
Whether watching baseball or undergoing heart surgery, Americans have bought a variety of goods and services to achieve happiness. Here is a provocative look at what they have chosen to purchase. Stanley Lebergott maintains that the average consumer has behaved more reasonably than many distinguished critics of ""materialism"" have suggested. He sees consumers seeking to make an uncertain and often cruel world into a pleasanter and more convenient place--and, for the most part, succeeding. With refreshing common sense, he reminds us of what many ""luxuries"" have meant, especially for women